2016
DOI: 10.1093/sleep/zsw037
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Function in Patients With Acute Tetraplegia and Sleep Disordered Breathing

Abstract: Sleep disordered breathing is highly prevalent following spinal cord injury and likely caused by the injury. Beyond the devastating physical consequences of spinal cord injury, neuropsychological dysfunction is also common. In both the able-bodied and chronic spinal cord injury patients, sleep disordered breathing impairs many areas of neuropsychological function. However, this has not been investigated in patients with acute injury. Study objectives: To investigate the relationship between apnea severity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 49 publications
3
16
0
Order By: Relevance
“…These findings have been attributed to breathing problems rather than to an impaired MT secretion. Similar conclusions have been reported in other studies in which the poor sleep efficiency has been related to sleep apneas and neuromuscular weakness that negatively affects respiratory function [41][42][43]. In any case, people with tetraplegia suffer sleep problems and poor quality of life [44]; moreover, these problems associated to the increased metabolic disorders (as described in the Introduction) place them in an increased risk for suffering stroke or myocardial infarction.…”
Section: Discussionsupporting
confidence: 83%
“…These findings have been attributed to breathing problems rather than to an impaired MT secretion. Similar conclusions have been reported in other studies in which the poor sleep efficiency has been related to sleep apneas and neuromuscular weakness that negatively affects respiratory function [41][42][43]. In any case, people with tetraplegia suffer sleep problems and poor quality of life [44]; moreover, these problems associated to the increased metabolic disorders (as described in the Introduction) place them in an increased risk for suffering stroke or myocardial infarction.…”
Section: Discussionsupporting
confidence: 83%
“…Recent data in individuals with acute cervical SCI reported that increased SDB severity was associated with worse attention, information processing, and short-term memory. 36 Despite this high rate of abnormal sleep and daytime symptoms, SDB remains underdiagnosed and undertreated in these patients. 37 Furthermore, commonly used questionnaires (eg, Berlin Questionnaire Sleep Apnea, Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale) are limited in their ability to identify patients with SCI/D likely to suffer from SDB.…”
Section: Clinical Evaluation Of Patients With Sci/d With Suspected Sdbmentioning
confidence: 99%
“…Partly because, many studies that find a relationship between OSA severity and cognitive deficits do not control for cognitive reserve, and the few that do, find no dose–response relationship . Of note, in a recent study that investigated the relationship between severity of apnoea and neuropsychological function in patients with acute‐onset tetraplegia and sleep‐disordered breathing, higher preinjury intelligence and being younger reduced the associations with sleep‐disordered breathing . However, these protective factors were insufficient to offset the damage to attention, immediate recall and information processing associated with sleep‐disordered breathing.…”
Section: The Relationship Between Osa Severity and Cognitive Dysfunctmentioning
confidence: 99%